Safety And Convenience Of Ethnomedicine For Influenza Disease In Toddlers In Bedulu Village, Gianyar District - Dewa Ayu Putu Satya Dewi; Ida Ayu Manik Partha Sutema; Putu Yudhistira Budisetiawan; Ni Putu Aryati Suryaningsih (Jurnal EduHealth, 2023)
The Ethnomedicine is a research method that is effective in terms of time and cost for obtaining new compounds. This has resulted in Etnomediicne research continuing, including Indonesia especially the Bali island. Etnomedicine which has been a traditional medicine from generation to generation in Bali, is known as Usada Bali. Balinese people use Usada Bali for various types of illnesses, for example Influenza. This type of research is descriptive qualitative with a Snowball Sampling. Data collection methods were use structured interviews and Focus Group Discussion (FGD). This research was collected on 23 informants in Bedulu Village, Gianyar Regency with data processing using Braun and Clarke thematic data analysis. The research results obtained 5 themes, including Etnomedicine of Influenza Disease in Toddlers 1) Boreh Kencur with mixed ingredients, 2) Boreh Kencur with mashed, 3) Onion oil with chopped, 4) Onion Oil with smeared, and 5) Dadap leaves. The safety and comfort results showed that all Etnomedicine Influenza Disease for Toddlers in Bedulu Village, Gianyar were concluded to be safe, while Beras Kencur with mashed and Onion Oil with chopped was concluded to be less comfortable because the ones used were not preferred.